MANAGEMENT OF INDIVIDUALS USING ASSISTIVE TECHNOLOGY - Athanasopoulou, Lambrine (International Journal For Research In Business, Management And Accounting, 2016)
In this paper, it is examined whether the individuals use assistive technology and indicatively what tools they use in their business environment or in their studies regarding the students of this research, increasing their productivity in their work, too. The sample is divided into two teams (Team A‟ & B‟), that means individuals with and without learning difficulties. The results supported the hypothesis that the individuals with learning difficulties used assistance technology in their work or in their studies in comparison with the adults without learning difficulties.